Legal Protection for People with Mental Illness as Victims and Perpetrators of Criminal Acts - Murtantyo Hutomo, Hery; Sura Anabertha Sembiring, Malemna (ARRUS Journal of Social Sciences and Humanities, 2023)
This study aims to determine the synchronization of legal protection arrangements for people with mental illness (ODGJ) and its forms of legal protection in the structure of Indonesian laws and regulations. This study used normative juridical research methods. The approach used in this study is the Statue Approach and Analytical Approach with the specification of research inventory of laws and regulations, legal synchronization , and legal discovery in concrete. The result revealed that legal protection for people with mental illness (ODGJ) in some cases has not shown a level of synchronization. It is concerned in several legal provisions, namely Article 28G paragraph (2) and 28I of the 1945 Constitution, Article 86 of the Mental Health Law Number 18 of 2014, Article 453 of Law Number 17 of 2023, Article 9 of Law Number 39 of 1999, Article 333, 304, 491, 44 paragraph 2 of the Criminal Code, and Ministry of Health Regulations (Permenkes) Number 54 of 2017. According to these results, it can be concluded that the efforts to prevent and overcome shackling action for people with mental illness are through a promotive, preventive, curative, and rehabilitative approach to the community about individuals with mental illness (ODGJ). The construction of a mental hospital with a criminal room that can accommodate treatments for people with a mental health condition with criminal convictions or routine treatments of people with a mental health condition who are convicted in detention cells. There are clear juridical qualifications between crime and offense so as not to cause juridical problems in its implementation.